Etiological spectrum of Heart Failure in a tertiary health care facility of Central Nepal - Bhattarai, Mahesh; Shah, Rakesh Kumar; Sainju, Nayan Kamal; Bhandari, Buna; Keshari, Sumir; Karki, Damber Bahadur (Nepalese Heart Journal, 2019)
Background and Aims: High-income countries have reported common causes of heart failure as ischaemic heart diseases, hypertension, valvular heart diseases, and cardiomyopathies. There are limited data available about epidemiology of heart failure in low-income countries like Nepal. The main objective of this study is to explore etiological spectrum of heart failure in Nepal. Methods: This cross-sectional study was conducted at the cardiology department of Kathmandu Medical College from April 15, 2019, to July 15, 2019. Data were collected from patients diagnosed as heart failure following the European Society of Cardiology criteria and having left ventricular ejection fraction less than 50% and classified into Heart failure with midrange or reduced ejection fraction. Diastolic heart failure, Cor-pulmonale, and stroke were excluded. The data were entered and analyzed in Statistical Package for Social Sciences 20.0 using descriptive and inferential statistics. Results: Among 132 heart failure patients (mean age: 63.9±13.9 years), around two-thirds (65.2%) had heart failure with reduced ejection fraction (ejection fraction of less than 40%) and one third (34.8%) had heart failure with mid-range ejection fraction (40 to 49%). Dilated cardiomyopathy was the leading cause of heart failure among nearly half (47.7%) of study participants, followed by valvular heart disease (19.7%), hypertensive heart disease (14.4%) and ischaemic heart disease (13.6%). Almost half of the study participants with dilated cardiomyopathy had severe left ventricular systolic dysfunction. (p<0.05). Conclusion: Dilated cardiomyopathy was the most prevalent cause of heart failure, followed by valvular heart disease in our study.